Peran Sumber Informasi dan Pengetahuan dalam Proses Inovasi : Pembelajaran dari Perusahaan sektor TPT - Dian Prihadyanti (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2013)
To deal with increasingly tight competition in this globalization, it is essential for firms to have dynamic change for increasing competitiveness. One attempt to improve competitiveness is through innovation. Sources of information and knowledge have important role in innovation process. Using two case studies of firms in textile and textile products (TPT), this paper seeks to examine the presence, types, and role of sources of information and knowledge in innovation process. Innovation is viewed as learning process configuring a loop which consists of problem finding, problem selecting, solution finding, and solution selecting process. Results of the study shows that sources of information and knowledge either internal or external haveimportant role in innovation process of the firms in TPT's sector. Utilization of appropriate and optimal sources of information and knowledge may become key factor of innovation for the firms. The broader the sources used by the firms, the higher the innovation level is. External parties play important role in supplying information and knowledge in the problemfinding and solution finding. Whilst, internal parties hold main role in problem selecting and solution selecting process.